(untitled) (Historia, 2021)
During the Battle of Sidi Rezegh on 23 November 1941, a large number of volunteers from the Union Defence Force (UDF) was taken prisoner by Axis forces. Between 2 000 and 2 500 of these men were transported to Italy on board the San Sebastian, an Italian cargo ship, which was torpedoed by HMS Porpoise on 12 December 1941. Following the attack, the San Sebastian ran aground on the Greek shore where Italian forces awaited the captives. The article places the San Sebastian incident in context by looking at the experience of battle and capture, as well as initial perceptions among prisoners-of-war (POWs) of their Italian captors. The behaviour of the Italian captain and many crew members led to a general sense of antagonism towards the Italians. The torpedoing of the ship and the increasing abhorrence towards their captors greatly influenced the way these POWs approached the remaining time in captivity, yet the individual responses from POWs prohibits simplified interpretations of the event. Relying on first-hand accounts provided by former POWs, memoirs and archival documents, this article presents an analysis of the different responses to the incident. Examples of conflict and cooperation between captives and captors are highlighted, as are cases of self-preservation, reprisal and aid to fellow POWs.